The Siamese Government's Responses to Western Forces at the Time of King Mongkut (1851-1868) = Polityka rządu syjamskiego względem zachodnich sił w okresie panowania króla Mongkuta (1851-1868) - Dung, Nguyen Tien (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Since the second half of the nineteenth century, when the Europeans with their gunboats appeared in almost evrey corners of Asian waters, the sovereignty of many countries in the region was put under the serious threats. Yet, Siam is the only country in Southeast Asia which successfully safeguarded its national independence and sovereignty. Most scholars have explained the success of Siam in terms of its unique positions as ?a buffer zone? between two competing colonial powers, namely the French and the British.
Keywords: Syjam; Mongkut (król Syjamu; 1804-1868); siły zachodnie; Siam; Western Forces